Overexpression miR‐211‐5p hinders the proliferation, migration, and invasion of thyroid tumor cells by downregulating SOX11 - Wang, Lei (J Clin Lab Anal, 2017)
PURPOSE: This study was aimed to investigate the relationship between miR‐211‐5p and SOX11, and the effects of their interaction on the proliferation, viability, and invasion of human thyroid cancer (TC) cells. METHODS: We used quantitative real‐time PCR (qRT‐PCR) to determine the expression of miR‐211‐5p and SOX11 mRNA in the thyroid tumorous and the adjacent tissues. The target relationship between miR‐211‐5p and SOX11 was confirmed using dual luciferase reporter gene assay. Flow cytometry, colony formation assay, Transwell assay, and MTT assay were performed to determine the cell‐cycle progression, cell apoptosis, proliferation and invasion, respectively. In addition, the tumor formation assay in nude mice was done to assess the effect of miR‐211‐5p on TC development in vivo. RESULTS: MiR‐211‐5p was underexpressed, whereas SOX11 was overexpressed in TC. The overexpression of miR‐211‐5p inhibited the expression of SOX11. The cell cycle was arrested and the proliferation as well as invasiveness was suppressed by exogenous miR‐211‐5p in TC cell line. The antitumor role of miR‐211‐5p was proved by the animal experiment. CONCLUSION: MiR‐211‐5p affected the viability, proliferation and invasion of TC by negatively regulating SOX11 expression.